A workplace physical activity program at a public university in Mexico can reduce medical costs associated with type 2 diabetes and hypertension Un programa de actividad física en el lugar de trabajo en una universidad pública de México puede reducir los costos médicos asociados a la diabetes tipo 2 e hipertensión - Pablo Méndez-Hernández; Darina Dosamantes-Carrasco; Carole Siani; Yvonne N Flores; Armando Arredondo; Irma Lumbreras-Delgado; Víctor M Granados-García; Edgar Denova-Gutiérrez; Katia Gallegos-Carrillo; Jorge Salmerón (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To assess the impact of a workplace leisure physical activity program on healthcare expenditures for type 2 diabetes and hypertension treatment. MATERIAL AND METHODS: We assessed a workplace program's potential to reduce costs by multiplying the annual healthcare costs of patients with type 2 diabetes and hypertension by the population attributable risk fraction of non-recommended physical activity levels. Feasibility of a physical activity program was assessed among 425 employees of a public university in Mexico. RESULTS: If 400 sedentary employees engaged in a physical activity program to decrease their risk of diabetes and hypertension, the potential annual healthcare cost reduction would be 138 880 US dollars. Each dollar invested in physical activity could reduce treatment costs of both diseases by 5.3 dollars. CONCLUSIONS: This research meets the call to use health economics methods to re-appraise health priorities, and devise strategies for optimal allocation of financial resources in the health sector. OBJETIVO: Evaluar el impacto de un programa de actividad física en el lugar de trabajo sobre la reducción de costos médicos directos relacionados con la diabetes tipo 2 y la hipertensión. MATERIAL Y MÉTODOS: Calculamos el potencial de la actividad física para reducir costos médicos, multiplicando los gastos médicos anuales que realizan diabéticos e hipertensos, multiplicados por la fracción atribuible poblacional asociada a un nivel de actividad física insuficiente. La factibilidad de ejecutar el programa fue evaluada en 425 trabajadores de una universidad pública en México. RESULTADOS: Si 400 trabajadores sedentarios participaran en un programa de actividad física recreativa para reducir su riesgo de diabetes e hipertensión, los costos médicos anuales reducirían en 138880 dólares. Cada dólar invertido en actividad física podría reducir 5.3 dólares en el tratamiento de ambas enfermedades. CONCLUSIONES: Esta investigación evidencia la utilidad de los estudios costoeconómicos en salud para optimizar los recursos financieros en este sector.